2017
DOI: 10.4184/asj.2017.11.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure to the Hand of a Spinal Interventionalist during Fluoroscopically Guided Procedures

Abstract: Study DesignProspective study.PurposeDuring fluoroscopically guided spinal procedure, the hands of spinal surgeons are placed close to the field of radiation and may be exposed to ionizing radiation. This study directly measured the radiation exposure to the hand of a spinal interventionalist during fluoroscopically guided procedures.Overview of LiteratureFluoroscopically guided spinal procedures have been reported to be a cause for concern due to the radiation exposure to which their operators are exposed.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…Thus, CNRB can be performed more safely under ultrasound guidance than fluoroscopic guidance. At 2 weeks and 12 weeks after the procedure, no significant differences were found in terms of pain relief with underlying nerve block and ultrasound-guided CNRB; nevertheless, reports revealed that, under ultrasound guidance, it is possible to avoid inadvertent puncture (5/55 cases under fluoroscopy and 0/55 cases under ultrasonography), with no additional radiation exposure 4,13,14) .…”
Section: Discussionmentioning
confidence: 96%
“…Thus, CNRB can be performed more safely under ultrasound guidance than fluoroscopic guidance. At 2 weeks and 12 weeks after the procedure, no significant differences were found in terms of pain relief with underlying nerve block and ultrasound-guided CNRB; nevertheless, reports revealed that, under ultrasound guidance, it is possible to avoid inadvertent puncture (5/55 cases under fluoroscopy and 0/55 cases under ultrasonography), with no additional radiation exposure 4,13,14) .…”
Section: Discussionmentioning
confidence: 96%
“…Although there are reports of reducing radiation exposure during PPS placement under fluoroscopy [ 16 , 17 , 18 , 19 , 20 ], direct radiation exposure to hands and fingers during surgery remains a major problem [ 21 , 22 , 23 , 24 , 25 ]. In this new procedure, the radiation exposure range is approached only during the insertion of preoperative K-wire into the outer edge of the pedicle.…”
Section: Discussionmentioning
confidence: 99%
“…Yamashita et al report in detail the amount of fluoroscopic radiation exposure during spinal examinations. It is noteworthy that the level of exposure encountered by the fingers near the exposure area is high (the total occupational radiation exposure doses received at the finger for a 3-month study period was 368 mSv) [ 21 , 22 ]. Bindal et al reported an average exposure time of 1.69 min per operative procedure, an average skin surface exposure of 59.5 mSv for patients irradiated with posteroanterior fluoroscopy, and an average exposure of 0.76 mSv for the surgeon’s dominant hand during fluoroscopy in MIS-TLIF [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term exposure to even low dose of radiation is now believed to have harmful effects, hence mitigating exposure to physicians performing interventional techniques is of utmost importance. Wearing lead aprons, maximizing the distance from the radioactive source, minimizing exposure time, avoiding magnification and increasing use of collimation are the main strategies to reduce radiation exposure with respect to ALARA principle [3,12] Aforementioned recommendations are often oversight; besides, physicians need reference level standards to assure quality controls. There is paucity of data regarding reference dose standards for epidural injections and available research have been focused on comparing radiation exposure for computed tomography or fluoroscopy-guided injections or conducted with relatively small sample sizes without available reference levels [13][14][15].…”
Section: Discussionmentioning
confidence: 99%